2015
DOI: 10.1038/hr.2015.71
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic signature of arterial stiffness in male patients with peripheral arterial disease

Abstract: Arterial stiffness is an independent determinant of cardiovascular risk and a marker of subclinical organ damage. Metabolomics may facilitate identification of novel low-molecular cardiovascular risk factors. The aim of the present study was to compare metabolic signatures and functional-biochemical characteristics of patients with peripheral arterial disease (PAD) and clinically healthy subjects. We studied 42 men with symptomatic PAD (aged 66±7 years) and 46 healthy men (aged 66±8 years). Aortic pulse wave v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 36 publications
(40 reference statements)
1
32
1
Order By: Relevance
“…29 Disturbances in fuel oxidation pathways have been previously linked to arterial disease. Zagura et al 11 used PWV to study male subjects with symptomatic peripheral arterial disease. They found a signature comprising lactate, carnitine and amino acids that were associated with PWV in their cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Disturbances in fuel oxidation pathways have been previously linked to arterial disease. Zagura et al 11 used PWV to study male subjects with symptomatic peripheral arterial disease. They found a signature comprising lactate, carnitine and amino acids that were associated with PWV in their cohort.…”
Section: Discussionmentioning
confidence: 99%
“…8 Certain traditional risk factors beyond ageing have been associated with arterial stiffness including insulin resistance/metabolic syndrome. 9,10 Several studies have reported alterations in fuel-metabolismrelated markers both in patients with clinically significant arterial stiffness [10][11][12] and in subjects with subclinical changes in arterial stiffness. 9,[13][14][15] One interpretation is that arterial stiffening may drive metabolic changes through impairments in distal tissue perfusion.…”
Section: Introductionmentioning
confidence: 99%
“…A higher AIX and aPWV has been shown to be correlated with 8-iso-prostaglandin F2a (F2-IsoPs), an indicator of oxidative stress, only in PAD patients and not in controls [ 44 ]. Likewise, in a metabolic profiling of PAD patients, oxidized LDL was independently associated with the aPWV, suggesting that arterial stiffening may be determined by the level of oxidative modifications [ 45 ]. Furthermore, arterial elasticity is a measure of vascular compliance and distensibility in addition to arterial stiffness; it can be quantified based on a modified Windkessel model, with C1 being a marker for large artery elasticity and C2 a marker for small artery elasticity [ 46 ].…”
Section: Arterial Stiffnessmentioning
confidence: 99%
“…This could be an innovative way to investigate the molecular basis of vascular disease. In this regard, recent metabolic phenotyping and profiling studies have obtained promising results on the atherosclerotic plaque of both carotid and coronary arteries and peripheral artery diseases [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%